The genetic and epigenetic contributions to the development of nutritional rickets - Ogunmwonyi, Innocent; Adebajo, Adewale; Wilkinson, Jeremy Mark (Frontiers in Endocrinology, 2022)
Nutritional rickets is an important disease in global health. Although nutritional rickets commonly manifests as bony deformities, there is an increased risk of life-threatening seizures secondary to hypocalcaemia. Dietary vitamin D deficiency is associated with the development of nutritional rickets among children and infants. This is especially true in populations of darker skinned individuals in high-latitude environments due to decreased ultraviolet light exposure, and in populations in tropical and subtropical climates due to cultural practices. A growing body of evidence has demonstrated that genetic factors might influence the likelihood of developing nutritional rickets by influencing an individual’s susceptibility to develop deficiencies in vitamin D and/or calcium. This evidence has been drawn from a variety of different techniques ranging from traditional twin studies to next generation sequencing techniques. Additionally, the role of the epigenome in the development of rickets, although poorly understood, may be related to the effects of DNA methylation and non-coding RNAs on genes involved in bone metabolism. This review aims to provide an overview of the current evidence that investigates the genetic and epigenetic determinants of nutritional rickets.